THE INFLUENCE OF GREEN MARKETING, KNOWLEDGE, AND PURCHASE INTENTION ON PURCHASING DECISIONS WARDAH COSMETIC USERS IN MATARAM - Baiq Indah Nurul Haqiqi; Yusi Faizathul Octavia; Ulfiyani Asdiansyuri (Fakultas Agama Islam Universitas Islam Al-Azhar, 2024)
This study aims to determine the effect of green marketing, knowledge, and buying interest on purchasing decisions for Wardah cosmetic users in Mataram. The sampling technique in this study was nonprobability sampling. The sample in this study amounted to 80 respondents, who were determined using a purposive sampling technique. The data in this study were analyzed using Multiple Linear Regression. Table results of this study indicate that the variables Green marketing, Knowledge, and Purchase Interest are stated to have a partial effect on the Purchasing Decisions of Wardah cosmetic users in Mataram. The green marketing variable has a t-count value (2.364) and a t-value (1.992). The knowledge variable has a t-count value (2,057) t-value table (1,992), and the purchase intention variable has a t-count value (5,643) with a t-value table (1,992). Simultaneously, the Green marketing, Knowledge, and Purchase Intention variables affect the Purchasing Decisions of Wardah cosmetic users in Mataram. The results obtained showed that F-count (92.895) is greater than the F-value table (2.72) with a significant value of 0.00, which is smaller than 0.05, and purchase interest has the most dominant effect on purchasing decisions compared to other variables, namely 0.554 and also a tcount value of 5.643.